Genome-wide analysis of Rf-PPR-like genes in Nicotiana tabacum and their potential roles in anther development - Wu, Mengting; Ji, Yan; Zhang, Chengbei; Du, Shuaibin; Gong, Ruqi; Wang, Jun; Li, Jiayi; Zhong, Qiu; Li, Yuan; Yang, Aiguo; Cheng, Yazhi; Zhang, Xingwei; et al. (Frontiers in Plant Science, 2025)
Pentatricopeptide repeat (PPR) gene family is one of the largest gene families in higher plants. The Restoration of fertility like (RFL) clade of the family plays a crucial role in restoring fertility of cytoplasmic male sterility (CMS) lines in plants. Common tobacco (Nicotiana tabacum L.) is an important economic crop of which the CMS hybrids have been widely used in commercial cultivation. However, the restorer line of tobacco and the regulatory mechanism of fertility restoration remain elusive. In addition, PPR and RFL genes have not been illustrated in common tobacco. In this study, a total of 1002 NtPPR genes were identified, of which 27 NtRFLs belonging to P subfamily were demonstrated. The collinearity analysis showed that a total of 15 pairs of NtRFL genes had collinear relationship and unevenly distributed in 9 linkage groups. Cis-element analysis revealed that a large number of environmental stress and phytohormone response elements were located in the promoter of NtRFLs. By combining the RNA-seq and qPCR analysis, NtRFL3 was further selected as the candidate gene due to its significantly higher expression at early anther development in the fertile line MF1. NtRFL3 was predicted to be localized in mitochondria and shared high sequence similarity with the known fertility-restorer PPR592 in petunia. Our results provided new gene targets for molecular breeding of tobacco restorer lines and for illustration of molecular mechanism on fertility restoration of plant CMS lines.